1978
DOI: 10.1139/f78-137
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 14C-benzene in Eggs and Larvae of Pacific Herring (Clupea harengus pallasi)

Abstract: Eggs and larvae of Pacific herring were exposed to low concentrations of 14C-labeled benzene, a soluble, aromatic component of crude oil. All life stages accumulated benzene from water in direct proportion to the initial exposure concentrations, reaching equilibrium within 6–12 h. Feeding larvae exposed to benzene through water and live food accumulated benzene initially from the water, then secondarily from the food. The maximum amount of benzene accumulated in tissues was inversely related to age. Eggs accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly the metabolism and/or depuration of toxicants was most likely slowed in the less developed life stages which lacked fully functional organs such as liver and gall bladder. Eldridge et al (1978) inferred from 14C labelled benzene uptake experiments that eleutheroembryos of herring, Clupea harengus pallasi, had much higher metabolic rates than embryos. However, in our study exposure to diluted and undiluted effluent revealed that the utilization of lipid rich yolk and excretion rates was probably less in embryos and eleutheroembryos in comparison to alevins after the ' swim-up ' phase.…”
Section: Elapsed Time (Days) Elapsed Time (Days)mentioning
confidence: 99%
“…Similarly the metabolism and/or depuration of toxicants was most likely slowed in the less developed life stages which lacked fully functional organs such as liver and gall bladder. Eldridge et al (1978) inferred from 14C labelled benzene uptake experiments that eleutheroembryos of herring, Clupea harengus pallasi, had much higher metabolic rates than embryos. However, in our study exposure to diluted and undiluted effluent revealed that the utilization of lipid rich yolk and excretion rates was probably less in embryos and eleutheroembryos in comparison to alevins after the ' swim-up ' phase.…”
Section: Elapsed Time (Days) Elapsed Time (Days)mentioning
confidence: 99%